Transcriptional regulation of ETV5 by mitogen-activated protein kinase via ETS-1 in human pancreatic cancer cells - Noguchi, Aya; Kimura, Masanobu; Saiki, Yuriko; Ishikawa, Tomohiko; Kokumai, Takashi; Omori, Yuko; Ono, Yusuke; Miszukami, Yusuke; Ishida, Masaharu; Mizuma, Masamichi; Nakagawa, Kei; Unno, Michiaki; et al. (Scientific reports, 2025)
Pancreatic cancer is characterized by constitutive activation of mitogen-activated protein kinase /extracellular signal-regulated kinase 1/2 (ERK1/2) driven by gain-of-function mutations of KRAS . Our previous transcriptome sequencing of ERK1/2-attenuated cultured pancreatic cancer cells unveiled numerous downstream genes activated by ERK1/2 including ETV5 . In this study, we explored the mechanism of transcriptional regulation of ETV5 by ERK1/2 in human pancreatic cancer cells. Detailed reporter assays uncovered a core promoter region spanning between − 350 and − 985 from the transcription start site of ETV5 as a strong responsive element to ERK1/2 activity. Moreover, ETS proto-oncogene 1, transcription factor (ETS-1) was found to bind to one of consensus binding sites in the core region and to promote ERK1/2-mediated upregulation of ETV5 . Investigation of functional significances of ETS variant transcription factor 5 (ETV5) expression in the pancreatic cancer cells revealed that ETV5 was associated with resistance to gemcitabine; while no significance in proliferation, migration, and invasion. ETV5 expression in pancreatic ductal adenocarcinoma tissues resected from patients undergoing neoadjuvant chemotherapy was associated with KRAS mutations, which was consistent with ETV5 as a downstream upregulated molecule of RAS-ERK1/2 pathway. This study elucidated the mechanism of ERK1/2-mediated transcriptional regulation of ETV5 in human cancer cells, which could contribute to understand pancreatic cancer pathobiology.